ANALISIS PENENTUAN HARGA JUAL TANAMAN SELADA PADA USAHATANI HIDROPONIK DI KELURAHAN HANGA-HANGA KABUPATEN BANGGAI - A Zaenuddin, Ruslan; Banaali, Askari; Rustiawati, Yuni (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2024)
Companies that produce a product in their production process need facts about how much costs are used in producing these products and at the same time are expected to be able to estimate the correct cost of goods sold and the products produced. The aim of this research is to find out how Andri Farm Hydroponics determines the selling price of hydroponic lettuce products using quantitative descriptive data analysis methods, where the full costing method is to calculate the cost of production and the cost-based pricing method is cost plus pricing to determine the price. sell to consumers. The selling price for lettuce plants according to Andri Farm Hydroponics is IDR 6,000, whereas according to the cost plus pricing method the selling price calculation is IDR 3,303. So the selling price for hydroponic lettuce plants gets a difference of IDR 2,697. So the results of Andri's hydroponic farm based on the full costing component of the selling price set by the company are higher than the selling price calculated based on the cost plus pricing method. This means that the pricing for Andri Farm's Hydroponic lettuce plants has met the minimum profit standards.